PASIEN KANKER PARU DENGAN SUPERIOR VENA CAVA SYNDROME (SVCS): LAPORAN KASUS ASUHAN KEPERAWATAN [CASE REPORT OF NURSING CARE FOR LUNG CANCER PATIENTS WITH SUPERIOR VENA CAVA SYNDROME (SVCS)] - Agnes Ardhia Garini; Anesya Aprilya Nahumury; Antonia Niken Rillya Aruan (Universitas Pelita Harapan, 2023)
Lung cancer is a collection of genetic alterations that result in the proliferation of respiratory epithelial cells.One of the complications of lung cancer is Superior Vena Cava Syndrome (SVCS) which arises due to obstruction of the superior vena cava by thrombus. The main priority in the care of lung cancer patients is to meet the their needs and to reduce the perceived complaints. In addition, if pulmonary complications occur with SVCS, nurses must be aware of common clinical manifestations, such as dyspnea and edema in the upper chest, arms, neck, and face. A 53-year-old man with post-craniotomy and biopsy-suspected occipital metastases extra presented with dry cough, weakness, and shortness of breath that worsened when he laid on his back and improved slightly when he sat, as well as swelling in the upper chest, arms, neck, and face. The patient was administered heparin 5000 U/24 hours after being diagnosed with meta-brain lung cancer and SVCS. Cancer infiltrates the mediastinal space, compresses the superior vena cava, and results in SVCS in the patient. The patient immediately administered an anticoagulant, such as heparin, based on the results of the assessment and supporting examinations. In addition, nurses provided nursing care based on the patient's response, such as managing dyspnea and assisting patients and families on how to minimize the side effects of heparin use. Patients with lung cancer should receive heparin due to the high risk of thrombosis followed by SVCS,which is also called as an oncology emergency. Nurses must continue to monitor the patient's condition and fulfill their educational responsibilities.BAHASA INDONESIA ABSTRAK Kanker paru adalah kumpulan perubahan genetik pada sel epitel saluran pernapasan yang mengakibatkan proliferasi sel. Salah satu komplikasi dari kanker paru adalah Superior Vena Cava Syndrome (SVCS) yang timbul akibat obstruksi vena kava superior oleh trombus. Peran utama dalam perawatan pasien kanker paru adalah memenuhi kebutuhan pasien maupun untuk mengurangi keluhan yang dirasakan. Selain itu, jika komplikasi pasien paru dengan SVCS, perawat harus memperhatikan manifestasi klinis yang sering terjadi pada pasien seperti dispnea maupun edema dibagian atas dada, lengan, leher dan wajah. Seorang laki-laki usia 53 tahun post kraniotomi dengan biopsi suspect metastase oksipital dextra datang dengan keluhan batuk tanpa adanya produksi sputum, dan lemas. Pasien juga mengalami perburukan sesak napas saat posisi supine dan sedikit membaik dalam posisi duduk serta adanya edema pada bagian superior mediastinum, lengan, leher dan wajah. Pasien terdiagnosa kanker paru metastasis otak dengan SVCS. Pasien mendapat terapi heparin 5000 U/24 jam. Kanker yang menginvasi ruang mediastinum dan menekan/menghimpit vena kava superior dan menyebabkan SVCS pada pasien. Hasil pengkajian dan pemeriksaan penunjang pasien mengarahkan pelaksanaan antikoagulan (heparin) dengan segera. Asuhan keperawatan dilakukan antara lain: pengelolaan dispnea dan mengajarkan pasien dan keluarga cara meminimalisir efek samping dari penggunaan heparin. Kanker paru sangat berpotensi terjadinya trombosis diikuti dengan adanya SVCS yang menjadi kegawatdaruratan onkologi sehingga pasien harus diberikan heparin. Perawat sangat perlu melakukan monitoring kondisi pasien melakukan perannya sebagai edukator.